Financial statements a step-by-step guide to understanding and creating financial reports - Ittelson, Thomas R. 1946 (Career Press, 2020)
This book teaches readers how to use specialized accounting vocabulary and makes accessible the structure and purpose of the three major numeric statements that describe a company's financial condition